Salario mínimo diferencial en Colombia: un análisis comparativo desde la categorización municipal, el costo de vida y otras propuestas (2021)
In this work we analyze the different proposals of the differential minimum wage that have been presented by different economic actors, including the Bank of the Republic and associated unions, we want to identify its elements and the problems that will favor the proposals given, and finally look at the feasibility of implementing it in Colombia, This analysis is carried out with the municipal categorization, which is a practical element that allows us to see in a more assertive way each municipality in Colombia, we want to visualize how viable is this implementation, what are its pros and cons and what are the elements that must be taken into account for its development.